2017
DOI: 10.1021/acscatal.6b03236
|View full text |Cite
|
Sign up to set email alerts
|

Expedient C–H Chalcogenation of Indolines and Indoles by Positional-Selective Copper Catalysis

Abstract: A versatile protocol for the C–H chalcogenation of indolines and indoles by means of copper catalysis was established. The C–H functionalization occurred selectively at the C7 position of indolines and exclusively at the C(2)–H bonds of indoles. The robust copper catalyst tolerated a wide range of functional groups and set the stage for the synthesis of diversely decorated indoles. Mechanistic studies were indicative of a SET-type mechanism and a facile C–H metalation being operative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(54 citation statements)
references
References 114 publications
1
47
0
Order By: Relevance
“…The C7 thiolation of indolines reported by Ackermann is also particularly interesting since no stoichiometric oxidant was used apart from air, requiring only a catalytic amount of Cu ( Scheme 145B ). 860 The same conditions proved effective also for thiolation and selenylation of indoles. Drawbacks of this protocol are the high temperature required and the relatively modest yields obtained for most examples.…”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 89%
“…The C7 thiolation of indolines reported by Ackermann is also particularly interesting since no stoichiometric oxidant was used apart from air, requiring only a catalytic amount of Cu ( Scheme 145B ). 860 The same conditions proved effective also for thiolation and selenylation of indoles. Drawbacks of this protocol are the high temperature required and the relatively modest yields obtained for most examples.…”
Section: Heterocyclic Dgs In C–h Functionalisationmentioning
confidence: 89%
“…Based on the literature and our experimental data, a plausible reaction pathway is outlined in Scheme . The first step is likely the oxygen mediated oxidation of Cu(I) catalyst, generating the active Cu(II) species.…”
Section: Methodsmentioning
confidence: 99%
“…A copper‐catalyzed C(7)−H functionalization of indoline was reported by Ackermann (Scheme ) . The authors demonstrated the thiolation of both the indoline and indole C−H bonds with excellent regio and chemoselectivity.…”
Section: C−heteroatom Bond Forming Reactionsmentioning
confidence: 99%
“…A copper-catalyzed C(7)À H functionalization of indoline was reported by Ackermann (Scheme 40). [78] The authors demon- strated the thiolation of both the indoline and indole CÀ H bonds with excellent regio and chemoselectivity. Diverse substituents like À Br, À Cl, À F, À Me on indole and/or indolines were well tolerated under optimized reaction conditions.…”
Section: Cà S Bond Forming Reactionsmentioning
confidence: 99%